2014
DOI: 10.1002/hep.26934
|View full text |Cite
|
Sign up to set email alerts
|

Population health impact and cost-effectiveness of monitoring inactive chronic hepatitis B and treating eligible patients in Shanghai, China

Abstract: Inactive chronic hepatitis B (CHB) carriers make up the largest group of hepatitis B virus-infected patients, and China bears the largest total CHB burden of any country. We therefore assessed the population health impact and cost-effectiveness of a strategy of lifelong monitoring for inactive CHB and treatment of eligible patients in Shanghai, China. We used a computer simulation model to project health outcomes among a population cohort of CHB based on age-specific prevalence of hepatitis B surface antigen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…Serum HBsAg seroprevalence rates in East Asia for ≥65 years are similar to that of younger age groups, yet a previous study from our locality showed patients of ≥65 years comprised only 3.4% of total CHB specialist clinic cohort, implying a considerable proportion of elderly CHB patients were probably not referred to appropriate specialist care. Drug non‐adherence, common in the elderly population, could be also an important factor.…”
Section: Discussionmentioning
confidence: 57%
“…Serum HBsAg seroprevalence rates in East Asia for ≥65 years are similar to that of younger age groups, yet a previous study from our locality showed patients of ≥65 years comprised only 3.4% of total CHB specialist clinic cohort, implying a considerable proportion of elderly CHB patients were probably not referred to appropriate specialist care. Drug non‐adherence, common in the elderly population, could be also an important factor.…”
Section: Discussionmentioning
confidence: 57%
“…It was not appropriate for advanced complications because of more than once for hospitalization and excess costs from outpatient. So annual costs of decompensated cirrhosis and hepatocellular carcinoma were estimated from studies on chronic hepatitis B (CHB) in China [31, 32], with the assumption made specifically for this study: annual costs for advanced complications of CHB patients are identical to CHC patients. Furthermore, the estimated annual costs for patients receiving liver transplant were derived from Chinese patients [33, 34].…”
Section: Methodsmentioning
confidence: 99%
“…These patients require lifelong surveillance by a physician experienced in the management of chronic liver disease as early antiviral therapy can prevent the progression of liver disease and HCC, 1, 4, 7 and has been shown to be cost effective in decision analysis models. 27 In one study, the risk of developing cirrhosis amongst chronic inactive carriers was 15% over 25 years. 28 It is important to also note that more than half (54%) of the mothers in our cohort who were tested were HBeAb positive and therefore are at risk for developing active hepatitis in the form of HBeAb positive/HBeAg negative chronic hepatitis.…”
Section: Commentmentioning
confidence: 99%